Tafsir Ringkas dan Penyederhanaan Tafsir: Transposisi dalam Tafsir Ringkas M. Quraish Shihab dan Kementerian Agama RI - Rahmatullah, Rahmatullah (Lajnah Pentashihan Mushaf Al-Qur'an, 2023)
This article examines the concise tafsir of the 30 chapters ( juz) by M. Quraish Shihab and the one published by the Ministry of Religious Affairs of the Republic of Indonesia. The article reveals that the concise tafsir is the result of simplifying a detailed tafsir made by the same author. Analyzed through Julia Kristeva’s theory of intertextuality, the simplification consists of three patterns of transposition. First, rearrangement, which involves reorganizing the discussion of tafsir by presenting a tafsir that is relatively similar but in a different form. Second, substitution, which entails replacing specific tafsir considered less relevant to modern society. Third, reduction, which involves minimizing particular tafsir that is controversial or appears complicated to understand. In the context of its emergence, the making of this tafsir is part of an effort to modernize tafsir in modern Indonesia. This simultaneously emphasizes the emergence of an awareness for the renewal of tafsir among Indonesian Muslims through the compilation of a concise, practical, and complete 30-chapter of tafsir that aligns with the real needs of modern society, rather than creating thematic tafsir.